2014
DOI: 10.1002/jobm.201400540
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome response ofLactobacillus sakeito meat protein environment

Abstract: Lactobacillus sakei is a heterofermentative species of lactic acid bacteria that is used in industrial meat fermentation. To investigate adaptation in a meat environment, whole-genome DNA microarrays were used to analyze the gene expression related to growth and survival of L. sakei strain La22 when grown in sarcoplasmic (S-) or myofibrillar (M-) protein-supplemented chemically defined medium (CDM). Differential expression was detected in 551 genes. Genes encoding enzymes involved in peptide hydrolysis were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Different efficiency in the utilization of arginine were also observed in two L. sakei strains (23K and LS25) grown in glucose limited medium; these differences were explained by the possible presence of two distinct ADI pathways, whose coexistence favored a more efficient arginine metabolism (McLeod et al, 2017). According to previous study, the ADI pathway was inhibited by low pH (Rimaux et al, 2011a; Xu et al, 2015). This trend was confirmed by the fact that higher arginine depletion was observed when sugars were not added, and, thus, when the medium was not acidified by microbial metabolisms of simple carbohydrates.…”
Section: Resultsmentioning
confidence: 85%
“…Different efficiency in the utilization of arginine were also observed in two L. sakei strains (23K and LS25) grown in glucose limited medium; these differences were explained by the possible presence of two distinct ADI pathways, whose coexistence favored a more efficient arginine metabolism (McLeod et al, 2017). According to previous study, the ADI pathway was inhibited by low pH (Rimaux et al, 2011a; Xu et al, 2015). This trend was confirmed by the fact that higher arginine depletion was observed when sugars were not added, and, thus, when the medium was not acidified by microbial metabolisms of simple carbohydrates.…”
Section: Resultsmentioning
confidence: 85%
“…Moreover, even though we found a high presence of this molecule at the end of ripening in I samples (1,100 g/kg, Table S4), Dainty et al (27) have reported that the higher presence of acetoin in meat is not unpleasant. Carbohydrate metabolism was the most prevalent pathway in I samples, most likely due to the predominant presence of the heterofermentative L. sakei (28), and carbohydrate pathways were found to be one of the main precursors of many volatile organic compounds (VOCs) such as acetate, acetoin, diacetyl, acetic acid, and isobutyric acid (1).…”
mentioning
confidence: 99%
“…Primers were designed and synthesized according to gene sequences on NCBI (Table S1 ). The gene‐expression levels were calculated via the 2 —△△Ct method (Xu et al., 2015 ), which was used to compare with the sequencing results of the transcriptome.…”
Section: Methodsmentioning
confidence: 99%